Rydberg Series Excitation of a Single Trapped Ca+ 40 Ion for Precision Measurements and Principal Quantum Number Scalings - Andrijauskas, J.; Vogel, J.; Mokhberi, A.; Schmidt-Kaler, F. (Physical Review Letters, 2021)
A complete set of spectroscopic data is indispensable when using Rydberg states of trapped ions for quantum information processing. We carried out Rydberg series spectroscopy for nS1/2 states with 38≤n≤65 and for nD5/2 states with 37≤n≤50 on a single trapped Ca+40 ion. We determined the ionization energy of 2 870 575.582(15) GHz, 60 times more accurately as compared to the accepted value and contradicting it by 7.5 standard deviations. We confirm quantum defect values of δS1/2=1.802 995(5) and δD5/2=0.626 888(9) for nS1/2 and nD5/2 states, respectively, which allow for unambiguous addressing of Rydberg levels of Ca+ ions. Our measurements confirm Rydberg ion scaling properties, e.g., for blackbody induced ionization, linewidths and excitation strengths.
CRIS-Team Scopus Importer:2023-03-27